2009
DOI: 10.1159/000223731
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Plasma Levels Are Not Altered in Major Depression

Abstract: Background: In patients with major depression, the function of most endocrine axes is altered compared to healthy subjects. The orexigenic hormone ghrelin, which shows higher plasma levels in females than males, interacts with several of these endocrine axes. In addition, ghrelin levels in depressed patients decrease with psychopathological improvement. Therefore, we hypothesized that ghrelin levels in patients with major depression would be higher than in healthy subjects. Methods: Nocturnal (20:00–07:00 h) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 102 publications
1
36
2
1
Order By: Relevance
“…Nevertheless, the results are inconsistent. While some publications found no difference in serum ghrelin in patients with major depressive disorders (Emul et al, 2007, Kluge et al, 2009, there is one report indicating higher serum ghrelin both in patients with major depressive episodes and in those with bipolar disordermanic episodes . Furthermore, some authors suggest that psychopathological improvement of major depression is associated with a significant decrease in serum ghrelin , Emul et al, 2007 whereas data obtained with sleep deprivation suggest that the beneficial effects of chronotherapeutic interventions in depression may be mediated by an increase of ghrelin (Schussler et al, 2006, Treuer, 2007.…”
Section: 2mentioning
confidence: 91%
See 1 more Smart Citation
“…Nevertheless, the results are inconsistent. While some publications found no difference in serum ghrelin in patients with major depressive disorders (Emul et al, 2007, Kluge et al, 2009, there is one report indicating higher serum ghrelin both in patients with major depressive episodes and in those with bipolar disordermanic episodes . Furthermore, some authors suggest that psychopathological improvement of major depression is associated with a significant decrease in serum ghrelin , Emul et al, 2007 whereas data obtained with sleep deprivation suggest that the beneficial effects of chronotherapeutic interventions in depression may be mediated by an increase of ghrelin (Schussler et al, 2006, Treuer, 2007.…”
Section: 2mentioning
confidence: 91%
“…Surprisingly little is known about the effects of chronic ghrelin exposure on these behaviours, forming a key aim of the present study. Even though, genetic and pharmacological studies suggest that ghrelin may be of clinical relevance for psychiatric conditions like mood disorders in man , Nakashima et al, 2008 some contradictory data have been published (Emul et al, 2007, Kluge et al, 2009). …”
Section: 2mentioning
confidence: 99%
“…Nocturnal ghrelin levels however did not differ between patients with depression and normal controls (Kluge et al, 2009a). After four weeks of antidepressive therapy with mirtazapine nocturnal ghrelin levels decreased in comparison to baseline (Schmid et al, 2006).…”
Section: Ghsrmentioning
confidence: 70%
“…Monteleone et al [24] reported considerable increase in salivary ghrelin following social stress protocol. Investigations on major depression cases show constant level for ghrelin [2] . Findings of present study for ghrelin levels of depressed (CMS) animals (Table 2) are in agreement with Chuang and Zigman [17] , Asakawa et al [19] , Kristenssson et al [20] and Monteleone et al [24] reports witch indicate that ghrelin can increase in chronic psychological or environmental stress, and various protocols for depression induce.…”
Section: Discussionmentioning
confidence: 95%
“…However, studies with adverse effects of depression on endocrine parameters are very limited. Also, these studies have focused mainly on major depression cases [1][2][3] not chronic or depression resulting from mild environmental stresses. So, studies on endocrine indices of various models of depression are necessary [4] .…”
Section: Introductionmentioning
confidence: 99%